2012
DOI: 10.1186/1750-1326-7-55
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of formyl peptide receptors in receptor for advanced glycation end products (RAGE) - and amyloid beta 1-42-induced signal transduction in glial cells

Abstract: BackgroundRecent studies suggest that the chemotactic G-protein-coupled-receptor (GPCR) formyl-peptide-receptor-like-1 (FPRL1) and the receptor-for-advanced-glycation-end-products (RAGE) play an important role in the inflammatory response involved in neurodegenerative disorders such as Alzheimer’s disease (AD).Therefore, the expression and co-localisation of mouse formyl peptide receptor (mFPR) 1 and 2 as well as RAGE in an APP/PS1 transgenic mouse model using immunofluorescence and real-time RT-PCR were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
1
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 43 publications
4
69
1
2
Order By: Relevance
“…Our own previous investigations revealed a vivid expression of mFPR2 in the mouse brain whereas the mFPR1 is endogenously only weakly detectable. 22 However, the results of our mortality study revealed a significant decrease in survival after pneumococcal meningitis for both mFPR1-and mFPR2-deficient mice but there were no difference between mFPR1 and mFPR2. These results are supported by another study using infection models: Gao et al 16 reported an increased susceptibility to Listeria monocytogenes for mFPR1-deficient mice as measured by increased mortality and bacterial load in spleen and liver compared with wild-type littermates.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Our own previous investigations revealed a vivid expression of mFPR2 in the mouse brain whereas the mFPR1 is endogenously only weakly detectable. 22 However, the results of our mortality study revealed a significant decrease in survival after pneumococcal meningitis for both mFPR1-and mFPR2-deficient mice but there were no difference between mFPR1 and mFPR2. These results are supported by another study using infection models: Gao et al 16 reported an increased susceptibility to Listeria monocytogenes for mFPR1-deficient mice as measured by increased mortality and bacterial load in spleen and liver compared with wild-type littermates.…”
Section: Discussionmentioning
confidence: 53%
“…37 Interestingly, the chemotactic G-protein-coupled FPRs interact with a menagerie of structurally diverse pro-inflammatory and anti-inflammatory ligands associated with different diseases, including amyloidosis, Alzheimer's disease, prion disease and HIV. 22,38,39 We compared the effect of mFPR1 or mFPR2 deficiency after pneumococcal meningitis. Sequence comparison of both receptors revealed a similarity of 63%.…”
Section: Discussionmentioning
confidence: 99%
“…The transfection and selection of HEK293 cells expressing FPRL1, hRAGE, or ⌬RAGE were described previously (37,38). The pcDNA3.1-RAGE plasmid containing a neomycin resistance gene was kindly provided by R. Donato (Perugia, Italy) (39).…”
Section: Reagentsmentioning
confidence: 99%
“…Moreover, Slowik et al (25) showed that formyl peptide receptors, to which amyloid-␤ can bind, interact with RAGE and augment the enhanced signal transduction of ERK1/2 in HEK293 cells. However, Emmprin and TLR2/4 do not directly interact with RAGE.…”
mentioning
confidence: 99%